Stargazers - Gibbons, Gail. (New York : Holiday House, 1992)
Tells what stars are, why they twinkle, how constellations were named, how telescopes are used to study stars, and more.
Elem. School Library Collection
School Library Journal
Book Links (A.L.A.)
4.3
K-3
Keywords: Astronomy -- Juvenile literature; Astronomy -- Observers' manuals -- Juvenile literature; Stars -- Observers' manuals -- Juvenile literature; Astronomy; Stars; Astronomy; Stars